A minimum fluid volume of 75 mL is needed to ensure adequacy in a pleural effusion: A retrospective analysis of 2540 cases. Issue 9 (24th July 2014) - Rooper, Lisa M.; Ali, Syed Z.; Olson, Matthew T.
<x xml:space="preserve">Abstract</x> BACKGROUND No consensus exists regarding minimum fluid volume for adequacy of benign pleural effusion specimens. Although any volume is acceptable if cytologic findings are malignant, the distinction between the absence of disease and false‐negativity is not straightforward in low‐volume specimens. Recent literature has offered conflicting results regarding what minimum volume is necessary. Moreover, no studies to date have evaluated this issue across a large series of specimens with a wide distribution of volumes. The objective of the current study was to determine the minimum volume of pleural fluid necessary for optimal cytopathological diagnosis. METHODS The authors identified 2540 pleural fluid specimens received between January 2000 and December 2009 and retrospectively reviewed their diagnoses and characteristics. Because of the large range of volumes (1 mL‐6500 mL), the cases were binned into 9 groups of roughly equivalent sample sizes. The malignancy fractions (percentage of cases with malignant diagnoses) were compared for each group. RESULTS The current study specimens had a median volume of 200 mL and an overall malignancy fraction of 20.1%. The malignancy fraction increased from 10.1% (95% confidence interval, 8.1%‐12.1%) for volumes < 5 mL to 23.3% (95% confidence interval, 20.0%‐25.8%) for volumes between 50 mL and 75 mL (P = .009). Specimens with volumes ≥ 75 mL had malignancy fractions independent of volume. In addition, ratios of benign or malignant diagnoses versus nondiagnostic and atypical results continued to increase with volume. CONCLUSIONS A fluid volume of ≥ 75 mL is required to eliminate the influence of specimen size on diagnostic adequacy. Although larger volumes do not appear to impact malignancy fraction, they do correlate with decreased nondiagnostic and atypical results. Cancer (Cancer Cytopathol) 2014;122:657–665. © 2014 American Cancer Society.